1900
DOI: 10.1002/zaac.19000230120
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Erscheinungen bei der Elektrolyse von Alkalichloridlösungen mit Diaphragma

Abstract: ROC1 0.3022 g insgesamt. Es war also die Menge der unterchlorigen Saure unverandert geblieben, und das anfanglich aus der Einwirkung des Alkalis auf das freie Chlor hervorgegangene Hypochlorit hatte sich fast vollstandig in Chlorat verwandelt. Nach 2 Stunden enthielt die Losung gar kein unterchlorigsaures Salz mehr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1924
1924
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Focusing presently on the chlorate production process, it is well-known that, among others, Oettel and Foerster and co-workers ,− studied the fundamentals of chlorate formation during electrolysis of chloride solutions at the turn of the 20th century. This work might be traced to early German investigations into industrial-scale chlor-alkali electrolysis for production of, for example, caustic soda, which is said to have started in 1884 .…”
Section: Selectivity For Oxygen and Chlorine Evolution In Chlor-alkal...mentioning
confidence: 65%
See 2 more Smart Citations
“…Focusing presently on the chlorate production process, it is well-known that, among others, Oettel and Foerster and co-workers ,− studied the fundamentals of chlorate formation during electrolysis of chloride solutions at the turn of the 20th century. This work might be traced to early German investigations into industrial-scale chlor-alkali electrolysis for production of, for example, caustic soda, which is said to have started in 1884 .…”
Section: Selectivity For Oxygen and Chlorine Evolution In Chlor-alkal...mentioning
confidence: 65%
“…During this time, it was also suggested that both reaction and direct oxidation of ClO – , the so-called primary chlorate formation, with no accompanying chloride formation, occurred simultaneously in alkaline solution, both reactions forming chlorate (the reaction is written as given by Foerster). This early research was conducted mainly using polished Pt electrodes, but experiments were also done with graphite electrodes, , rough Pt electrodes, and Pt–Ir alloy electrodes. , Foerster recommended the Pt–Ir electrode, rather than graphite, in chlorate and chlor-alkali production, based on its superior stability. These early studies were often careful and detailed studies of the chemistry, often including measurements of both evolved oxygen gas and liquid phase hypochlorite, chlorate, and perchlorate.…”
Section: Selectivity For Oxygen and Chlorine Evolution In Chlor-alkal...mentioning
confidence: 99%
See 1 more Smart Citation